Low cost system for analysis and evaluation of movement em lower members through processing of images and video - Auccahuasi, Wilver (2020)
The evaluations in the development of the treatment to be able to recover the motor activity, it is considered of utmost importance in the rehabilitation of lower limbs, the state of the art allows us to evaluate various techniques and commercial products available for the evaluation of the movement and with emphasis on the members inferior, commercial products have the disadvantage of the high cost, which does not allow small medical offices to be able to implement these types of solutions, in this paper we propose a mechanism to evaluate the movements of lower limbs at a very low cost, the The proposal is based on equipment and components that are commonly used, economical and easily acquired; One of its main components is the passive marker that is composed of "expanded polystyrene" that has a half-sphere shape and is placed in the joint to be analyzed, complements the solution a video camera and a recording unit that records the video at least about 30 images per second. As a computational tool, Matlab software and its image processing library were used, where various algorithms could be designed to obtain a graph of the movement of the markers based on the video image. In the tests carried out, it was possible to register and analyze the movement, considering the member and the joint that you want to study, in that concept it was possible to register a side view of the person at the moment you are walking and therefore the joint is related to the marker. The proposed methodology is applicable for a single reference plane, if you want to analyze several reference planes simultaneously, it is necessary to increase the number of cameras, we conclude with the presentation of the conclusions that were obtained when conducting the investigation as well as indicating the How to scale the solution.